Leveraging ICT for mobility future in a region in transition: the case of Piedmont - Sylvie Occelli; Alessandro Sciullo (Netcom)
Current challenges of mobility in urban and regional areas call for new approaches to the analysis of the transportation system. Technological progress and spreading of Information and Communication Technologies (ICT) provide ground to the idea that a digital-age transportation system can be put in place. The text aims to contribute to the discussion of these changes, thus helping conceiving ICT based initiatives oriented at mobility improvements. A conceptual framework of mobility is proposed which highlights some potentials of ICT impacts and recalls the main determinants of mobility. Using that framework as a background, insights into mobility changes in the Piedmont region are discussed. Building upon previous studies of Internet usage, the results of an investigation into the role of the Internet to relax constraints in social practices are also mentioned as they offer interesting clues for designing new approaches to mobility.